A screen of FDA-approved drugs identifies inhibitors of protein tyrosine phosphatase 4A3 (PTP4A3 or PRL-3) - Dylan R. Rivas (Nature Portfolio, 2021)
Abstract Protein tyrosine phosphatase 4A3 (PTP4A3 or PRL-3) is highly expressed in a variety of cancers, where it promotes tumor cell migration and metastasis leading to poor prognosis. Despite its clinical significance, small molecule inhibitors of PRL-3 are lacking. Here, we screened 1443 FDA-approved drugs for their ability to inhibit the activity of the PRL phosphatase family. We identified five specific inhibitors for PRL-3 as well as one selective inhibitor of PRL-2. Additionally, we found nine drugs that broadly and significantly suppressed PRL activity. Two of these broad-spectrum PRL inhibitors, Salirasib and Candesartan, blocked PRL-3-induced migration in human embryonic kidney cells with no impact on cell viability. Both drugs prevented migration of human colorectal cancer cells in a PRL-3 dependent manner and were selective towards PRLs over other phosphatases. In silico modeling revealed that Salirasib binds a putative allosteric site near the WPD loop of PRL-3, while Candesartan binds a potentially novel targetable site adjacent to the CX5R motif. Inhibitor binding at either of these sites is predicted to trap PRL-3 in a closed conformation, preventing substrate binding and inhibiting function.